Lactosylceramide-accumulation in lipid-rafts mediate aberrant-autophagy, inflammation and apoptosis in cigarette smoke induced emphysema - Bodas, Manish; Min, Taehong; Vij, Neeraj (Apoptosis (London), 2015)
Ceramide-accumulation is known to be involved in the pathogenesis of chronic inflammatory lung diseases including cigarette smoke-induced emphysema (CS-emphysema) but the exact sphingolipid metabolite that initiates emphysema progression remains ambiguous. We evaluated here a novel role for the sphingolipid, lactosylceramide (LacCer), as a potential mechanism for pathogenesis of CS-emphysema. We assessed the expression of LacCer, and LacCer-dependent inflammatory, apoptosis and autophagy responses in lungs of mice exposed to CS, as well as peripheral lung tissues from COPD subjects followed by experimental analysis to verify the role of LacCer in CS-emphysema. We observed significantly elevated LacCer-accumulation in human COPD lungs with increasing severity of emphysema over non-emphysema controls. Moreover, increased expression of defective-autophagy marker, p62, in lung tissues of severe COPD subjects suggest that LacCer induced aberrant-autophagy may contribute to the pathogenesis of CS-emphysema. We verified that CS-extract treatment significantly induces LacCer-accumulation in both bronchial-epithelial cells (BEAS2B) and macrophages (Raw264.7) as a mechanism to initiate aberrant-autophagy (p62-accumulation) and apoptosis that was rescued by pharmacological inhibitor of LacCer-synthase. Further, we corroborated that CS exposure induces LacCer-accumulation in murine lungs that can be controlled by LacCer-synthase inhibitor. We propose LacCer-accumulation as a novel prognosticator of COPD-emphysema severity, and provide evidence on the therapeutic efficacy of LacCer-synthase inhibitor in CS induced COPD-emphysema.